Allium hooshidaryae (Alliaceae); Chemical compositions, biological and ethnomedicine uses. (28th June 2021) - Hafez Ghoran, Salar; Rahimi, Hero; Kazemi, Aboozar; Scognamiglio, Monica; Naderian, Moslem; Iraji, Aida; Bordbar, Firouzeh
Abstract: Ethnopharmacological relevance: Allium hooshidaryae (sect. Pseudoprason ) is a wild plant in northwestern Iran. The plant is traditionally used, besides as spice, also for its medicinal properties. Aim of the study: Due to the shortcoming evidence in scientific research and the importance of this plant in folk medicine, this study aims to assess the chemical compositions and biological activities, which have no longer reported to date. Materials and methods: The bulbs of A. hooshidaryae were collected from West Azerbaijan, Iran. The plant essential oil was obtained by hydrodistillation using Clevenger-type apparatus according to the European pharmacopeia. The plant hydromethanolic extract was obtained using maceration method. The volatile oil compositions of A. hooshidaryae bulbs were evaluated by use of combined gas chromatography/flame ionization detector (GC/FID) and gas chromatography/mass spectrometry (GC/MS) techniques. Furthermore, different biological activities of the yielded essential oil and hydromethanolic extract were in vitro evaluated. The antibacterial and antifungal activities were assessed using disc diffusion assay, tube dilution assay, minimal inhibitory concentration (MIC), minimal bactericidal concentration (MBC), and minimal fungicidal concentration (MFC). The cytotoxic activities were assayed by reduction of 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide (MTT) toward two human cancerous cell lines (MOLT-4 and MCF-7). Antioxidant activity was investigated using 2, 2-diphenyl-1-picrylhydrazyl (DPPH ) radical scavenging assay. Results: GC/FID and GC/MS analyses allowed detecting 62 components in the A. hooshidaryae essential oil representing the 91.87% of the total oil. The volatile compounds were identified by comparison of the relative retention indices (RRI), mass spectra with those in NIST08/NIH and Wiley (257 and 7 L) libraries and co-elution with authentic samples where available. Surprisingly, the most abundant compound was obtained as menthol (19.0%) followed by carvacrol (10.1%), menthone (6.4%), methyl (methylthiomethyl) disulfide (4.2%), dimethyl disulfide (3.8%), and thymol (3.8%). Contrary to the other Allium species enriched by sulfur compounds, just three compounds accounting for 10.7% of the total oil were obtained as the sulfur-sulfur bond containing components (Dimethyl disulfide, Methyl (methylthio) methyl disulfide, Bis-methylthiomethyl disulfide). The hydromethanolic extract of A. hooshidaryae showed higher anti-radical (IC50 DPPH of 9.81 μg/mL) and cytotoxic (for MOLT-4 and MCF-7, IC50s were 76.3 and 128.6 μg/mL, respectively) activities rather than that of the obtained essential oil (IC50 DPPH of 39.9 μg/mL; IC50 MOLT-4 of 109.2 μg/mL, and IC50 MCF-7 of 297.5 μg/mL). While, the essential oil exhibited the anti-Staphylococcus aurous and anti-Escherichia coli activities approximately the same as Chloramphenicol (positive control). The MIC values were 31.25 and 62.5 μg/mL and the disk inhibition zone values were 23 and 21 mm, respectively. In addition, Candida albicans had moderate sensitivity (MFC of 62.5 μg/mL) for the essential oil. Conclusions: The hydromethanolic extract of A. hooshidaryae shows the potency to be used for food protection in addition to further cytotoxic investigations. Associated with antimicrobial abilities of both A. hooshidaryae products, the compatible results was observed with the traditional claim having being not investigated to date. These findings will facilitate the development of A. hooshidaryae for further deep investigations. Graphical abstract: Image 1 Highlights: Analysis of Allium hooshidaryae essential oil (EO) composition. Menthol and carvacrol, the most abundant components in A. hooshidaryae EO. Antimicrobial, antioxidant, and cytotoxic assays for both EO and plant extract. The hydromethanolic extract shows high activities rather than the essential oil.